PENGETAHUAN AKUNTANSI, PERTIMBANGAN PASAR KERJA, PENGHARGAAN FINANSIAL DAN MINAT MENJADI AKUNTAN PUBLIK - Putu Darma Mahayuda; I Dewa Nyoman Badera (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2025)
Menurut data dari Pusat Pembinaan Profesi Keuangan, jumlah pegawai negeri di Indonesia menurun, sementara kebutuhan bisnis terkait pegawai negeri terus meningkat. Bisnis membutuhkan opini audit untuk menilai literasi keuangan mereka. Akuntan publik merupakan tenaga profesional yang diakui secara legal oleh menteri keuangan guna menjalankan tugas dalam ranah publik, dengan maksud utama menyampaikan data keuangan suatu entitas. Sebanyak 246 orang yang terpilih sebagai partisipan penelitian ini. Penelitian ini menggunakantmetode sensus, artinya seluruhtpopulasi yang relevan dengan penelitian diperhitungkan tanpa pengambilan sampel. Data yang terkumpul dianalisis melalui penerapan teknik Partial Least Squares (PLS), memanfaatkan perangkat lunak SmartPLS untuk pemrosesan statistik. Berdasarkan hasil penelitian, terdapat pengaruh yang kuat dan positif dari kesadaran masyarakat terhadap akuntansi terhadap ketertarikan individu. Contohnya, perkembangan dalam sektor ketenagakerjaan dan sektor finansial memberikan dampak signifikan terhadap tingkat kepercayaan masyarakat. Temuan ini memberikan kontribusi terhadap pemajuan Theory of Planned Behavior (TPB).According to data from the Center for Financial Profession Development, there are fewer public accountants in Indonesia even though the demand for their services is still growing. Businesses require audit opinions to assess the fairness of their financial statements. A public accountant is a registered professional who has been given permission by the Finance Minister to do public accounting work. The primary job of a public accountant is to provide their judgment on how fair a company's financial statements are. The research participants consisted of 246 individuals who were enrolled as accounting students in the academic batch of 2021. This study employed a census approach, meaning that all members of the identified population were included as subjects in the research. Data analysis was carried out using the Partial Least Squares (PLS) method, specifically utilizing the SmartPLS software to process and interpret the information collected. The results indicate that possessing a strong and comprehensive understanding of accounting significantly and positively influences a student’s intention to pursue a career as a public accountant. Financial rewards and diligent effort, along with market conditions, also play a meaningful and favorable role in shaping students’ intentions to become public accountants. This research adds valuable insight to the theory of planned behavior (TPB) and helps to expand its application.